Clearing, "Wasting, " and Regreening: An Environmental History of Bare Hills in Central Vietnam. Issue 4 (20th September 2018) - Biggs, David
Abstract : A recent trend of regreening formerly bare hills in central Vietnam is often described in the media as a form of recovery from 1960s wartime destruction. However, this modern framework of wartime "wasting" and regreening obscures a longer history of bare hills. Colonial explorers noted eroded slopes in 1877, and imperial land surveyors described stretches of "idle, fallow land" decades earlier. This article describes a longer history of a "wasteland" not only to challenge a presentist framing of environmental decline but also to recognize the historic roles people played in producing these spaces, often in response or resistance to state policies. Colonial engagements with land clearing and customary uses of "open" lands gave shape to colonial visions of "wasteland" and later spurred colonial environmentalist critiques, even calls for a new form of green colonialism via exotic tree plantations. Writing the history of such a "wasteland" is one way to decenter imperial, colonial, and nationalist teleologies that tend to emphasize the environmental "footprints" of state actions but not the reverse. This history of "bare hills" draws from a mix of historical sources to show how people produced this "wasteland" and why, at times, they maintained it despite state efforts at reclamation.